Preliminary validation of the perceived ethnic discrimination questionnaire community version (PEDQ-CV) - Rosnah Ismail; Pang, Vincent Ah Fook; Kntayya Mariappan; Balan Rathakrishnan; Ferlis Bahari; Budi Anto Mohd Tamring; Joki Perdani Sawai (Universiti Malaysia Sabah, 2011)
This research was conducted to test the psychometric properties of the Perceived Ethnic Discrimination Questionnaire-Community Version (PEDQ-CV). Psychometric tests of the PEDQ-CV included the internal consistency reliability by using Alpha Cronbach and construct validity by using factor analysis. The actual research was conducted on students on the main campus of Universiti Malaysia Sabah, Universiti Malaya, Universiti Kebangsaan Malaysia and Universiti Malaysia Sarawak. A total of 700 students from various ethnicities were recruited as respondents in this research. Questionnaires which comprised of different aspects of perceived ethnic discrimination were distributed to the respondents. The Alpha Cronbach coefficient reliability and factor analysis were analyzed using the SPSS version 17.0. The researchers used the internal consistency Cronbach Alpha method to determine the reliability of the instrument P EDQ-CVand its sub-scales. Research showed that the Cronbach Alpha for the scale of Lifetime Discrimination is 0.94 and this value indicates high internal consistency. Apart from testing the Cronbach Alpha for the Lifetime Discrimination scale, our research group also compared the Cronbach Alpha by Contrada (2001), Appel (2003), Brondolo (2005) and Pilot Study (2009) with the current research (2010) for the scales of Discrimination in the media, Discrimination against family members, Discrimination in different settings and Past week discrimination. While the result of construct validity through factor analysis showed that factors that were formed by our group is similar to the factors that was formed by Contrada (2001), Appel (2003) and Brondolo (2005). As a consequence from the finding of this research, the implication and suggestions are also proposed